Randomized controlled trial of the intraligamental use of a local anaesthetic (lignocaine 2%) versus controls in paediatric tooth extraction - HELEN M. SAMMONS, VANESSA UNSWORTH, CLAUDIA GRAY, IMTI CHOONARA, JANINE CHERRILL, & WILLIAM QUIRKE (IAPD and Blackwell, 2007)
Pain following dental extraction in children has now become better recognized and can be a cause of distress to both the child and their parents. Previous studies suggest that 33% of 5- to 12-year-old children experience moderate to severe pain, as assessed by their parents, following removal of primary teeth.